Aplicación de un sistema de costos ABC en la empresa de servicio de asesoramiento de seguridad y salud ocupacional ECUAPREVEN ubicada en la ciudad de Quito. - Cueva Madril, Brayan Alberto (2020)
This integrating project has been developed in the Ecuapreven company, in Quito, Pichincha province, with the purpose of issuing real and accurate information on the cost generated by each of the activities in the provision of advisory services, health and safety training occupational. The development of this work was designed to design a system of costs for ABC activities in order to determine the real cost of the services offered by Ecuapreven, which helped us to verify that the company does not know which activities generate the greatest economic value , the price estimation for each service is taken empirically and based on the prices of the competition without taking into account the activities that can generate significant value at the time of performing any type of service, so the ABC system allowed to know each activity and the value that it generates for its respective service process, the materials that are used in the provision of each service must be considered and used in the best way so as not to cause both economic and material lises, which in the future become an expense that directly harms the company. Through the aforementioned topic we have been able to establish the items that intervene in the activities with greater accuracy, knowing in this way the value, time and the necessary people involved in the provision of the services offered by the company. Through the ABC cost system, the actual sale price of the service receivable could be established in companies in both the public, private, and popular and solidarity economy sectors, which are in need of requesting the service in occupational health, counseling and training, in the same way verify that with the application of the system you can optimize resources and maximize profits; during a certain period.